Control of Salmonella Dublin in a bovine dairy herd. (1st June 2021) - Kent, Emily; Okafor, Chika; Caldwell, Marc; Walker, Tate; Whitlock, Brian; Lear, Andrea
Abstract: Salmonella enterica serovar Dublin ( S . Dublin) was diagnosed in a dairy herd after signs of acute gastroenteritis and sepsis. Two hundred eighty‐three Holstein cattle were sampled resulting in 700 observations, and serology for S . Dublin was performed. Holstein cattle sampled were divided by origin and arrival date to determine on‐farm exposure. Prevalence estimates were calculated and compared with control measures implemented on the dairy during the outbreak. One group of cows, presumed to be the original carrier animals, had the highest overall seroprevalence (76.5%). Seroprevalence decreased throughout the study, coinciding with testing and management changes. This report documents biosecurity measures that identified S . Dublin after the purchase of subclinical carrier cattle and the steps taken to successfully control herd transmission.